Project management in Zakat distribution - Syed Yusuf, Sharifah Norzehan; Said, Jamaliah; Bahrom, Hassan; Abdul Halim, Hazlina (2012)
Zakat Institutions are bodies that exist in Muslim societies, where their functions are to manage the social welfare of those in need. The core activities of zakat institutions are collecting compulsory contributions from eligible Muslims and distributing them to the rightful beneficiaries. These organizations provide various kinds of assistance such as food, shelter, health and education to rightful beneficiaries. Zakat assistance can be given in cash and also in kind. Now that some of the funds are distributed in kind, many projects such as permanent and temporary housing benefits, nursing homes, orphanages and schools' buildings are being erected. These projects utilised the fund from zakat collection. Thus effective and efficient use of zakat funds for these projects is very important however it is often neglected. This study uses qualitative case study research methods to explore how projects (distribution in kind) for zakat beneficiaries are being executed and managed. The finding shows that the demarcation of responsibility in managing distribution projects contributes to implementation friction in managing the execution distribution projects for Lembaga Zakat Selangor. It was also found that project management monitoring is performed by different department and final conclusions on the progress takes longer time to be resolved.